A Mycobacterium tuberculosis secreted virulence factor Rv1435c/hsr1 disrupts host snRNP biogenesis - Komal Chauhan; Dipanwita Datta; Yogita Kapoor; Nishat Passricha; Ravi Dutt; Naresh Arora; Mrinmoy Das; Kavya Rao; Lakshyaveer Singh; Arunima Gautam; Raman Deep Sharma; Binayak Sarkar; et al. (Proceedings of the National Academy of Sciences, 2025)
Transcriptional adaptation drives the host responses to Mycobacterium tuberculosis ( Mtb ) infection. However, Mtb alters host RNA splicing to quench host antibacterial responses, the mechanism for which remains unknown. Here, we report a mechanism whereby a secreted Mtb protein interferes with the biogenesis of key spliceosomal components. A high-throughput yeast-2-hybrid screen identified several Mtb -secreted proteins interacting with the host RNA splicing factors (SFs). Through custom-designed in-cell assays, we show that one of those proteins, Rv1435c/hsr1 (host splicing regulator 1), targets specific exon-skipping events. The Mtb Rv14345c/hsr1 facilitates direct interaction between Mtb phagosomes and U5 snRNA and SNRPF, key components of the snRNPs. Genetic deletion of Rv1435c/hsr1 reverses the specific exon-skipping events caused by WT Mtb infection. The Δ hsr1 strain shows compromised growth during ex vivo infection in macrophages and in vivo infection in mice. Tissue sections from the WT Mtb or Δhsr1 -infected mice showed significant hsr1-dependent SNRPF staining, a phenomenon also noted in the human intestinal tuberculosis (ITB) biopsies. Thus, hsr1 is a virulence factor that disrupts host snRNP biogenesis for pathogenesis. The splicing regulators from the host and pathogen are novel targets for antituberculosis therapy.